Moacyr Scliar : autobiografia e cura - Fernandes, Helena de Moraes (2022)
The theme of this thesis is the relationship between Autobiography and Healing for Moacyr Scliar. The research question is: will the author's autobiography allow identifying the Cure for the construction of himself and his Literature? This question leads to the investigation that makes visible a robust sample of the autobiographical set of scliariana's work, previously dispersed or not identified with the genre. For that, the organizing and aggregating elements are the meanings about healing for the author who, due to his historical and intellectual path, refers to Freud’s (1856-1939) and Jung’s approaches (1875-1961). The thesis formulated is that the autobiography is dissolved in the doctor-writer's work, to tell about himself, in a kind of selfdiagnosis, and to others, establishing healing attributes to his literary reading and writing. This is supposed, among several reasons verified here, among them because Scliar has chosen Public Health as a vocation, the hypothesis is that the autobiography (declared and undeclared) will reveal the subject of healing as an instrument of affirmation of its Identity History (LEJEUNE, 2008). The main goal of this research is to investigate, in Scliar's autobiographies, Healing as a guiding subject for the construction of the self (the author) and his Literature. The method is bibliographic and documentary, with a qualitative and exploratory approach, in which essay writing is observed as relevant to the analysis. The theoretical frameworks are Barthes (2004); Foucault (1992); Chartier (2012), Willemart (2005, 2019a, 2019b), Petit (2013) and Lejeune (2008). The research reveals that literature, for Scliar, is healing when: a) when writing in the first person through the voice of other narrative instances, he depresses reality through imagination, through the freedom authorized by fiction; b) appeases his own anxieties about death, by the feeling of accomplishment (so dear to Scliar) by recognizing that he would be leaving a legacy of overcoming related to the pain of the Jewish condition; c) is a self-diagnosis instrument and d) contributes to medical practice in interaction with patients. The research is justified because it contributes to investigations on the interface between Literature and Medicine, the transposition of healing to the study of literature (from autobiography), to medical self-care and to the optimization of doctor-patient relationships. This thesis is part of the Research Studies of Production and Reception of the Literary Text, of the Postgraduate Program in Letters of the University of Passo Fundo, is guided by Dr. Miguel Rettenmaier da Silva and it has the support of CAPES through the Postgraduate Support Program for Community Institutions of Higher Education (PROSUC) in modality II.